Targeting Notch signaling pathways with natural bioactive compounds: a promising approach against cancer - Yang, Jia; Sun, Qihui; Liu, Xiaoyun; Yang, Yong; Rong, Rong; Yan, Peiyu; Xie, Ying (Frontiers in Pharmacology, 2024)
Notch signaling pathway is activated abnormally in solid and hematological tumors, which perform essential functions in cell differentiation, survival, proliferation, and angiogenesis. The activation of Notch signaling and communication among Notch and other oncogenic pathways heighten malignancy aggressiveness. Thus, targeting Notch signaling offers opportunities for improved survival and reduced disease incidence. Already, most attention has been given to its role in the cancer cells. Recent researchwork indicates that signaling molecules affected by natural bioactive compounds are associated with or interact with the Notch pathways, suggesting a potential connection between Notch activation and tumor advancement shows that natural bioactive compounds can change signaling molecules that are linked to or interact with the Notch pathways. This suggests that there may be a link between Notch activation and the growth of tumors. Here, we sum up the natural bioactive compounds that possess inhibitory effects on human cancers by impeding the Notch pathway and preventing Notch crosstalk with other oncogenic pathways, which provoke further study of these natural products to derive rational therapeutic regimens for the treatment of cancer and develop novel anticancer drugs. This review revealed Notch as a highly challenging but promising target in oncology.